Adaptability of ASEAN states’ political security concept in the post-Cold War under a theory of social evolution analysis - Yuhong Li; Junze Feng; Anguang Zheng (Masyarakat, Kebudayaan dan Politik, 2023)
This study attempts to explain the changes in the adaptation of ASEAN states to security norms since the Cold War. This study focuses on qualitative research methods, mainly “process tracking” and “historical comparison.” After the end of the Cold War, the ASEAN states did not immediately adopt the ASEAN framework for security cooperation, but still followed a certain degree of survival instinct. With the strengthening of ASEAN’s normative power, the situation of security cooperation between Southeast Asia and other major states in the region has begun to be dominated by ASEAN. This change has not only led to changes in the security habits of ASEAN states but also prompted ASEAN states to gradually adapt to the security norms based on the ASEAN framework. The changes in the adaptability of ASEAN states to security norms illustrate the fact that ASEAN norms (ASEAN Way) are spread from another perspective, and also show the reasons why ASEAN can advance toward a security community. On the whole, the development of security norms of ASEAN states after the Cold War shows a direction of social evolution, and it is a kind of convergent evolution. With the influence of the external environment, ASEAN states “choose” ASEAN norms (ASEAN Way) to obtain security, and the ASEAN Security Community finally becomes a form of “inheritance”.